Longitudinal seismic responses of large diameter shield tunnel crossing liquefied bank slope - Xiaoxiong Li; Haiyang Zhuang; Bin Ruan; Kai Zhao; Guoxing Chen (Scientific Reports)
Abstract The lateral spread of the fluvial terraces due to liquefaction can cause tremendous physical damage to the underground structure. This paper designs a liquefaction slippage site and discusses the feasibility of the generalized response displacement method for investigating the seismic response of shield tunnels in liquefaction slippage areas. According to the actual shield tunnel project across the lower reaches of the Yangtze River, a 4.8-km large-scale liquefaction site and a refined beam-spring shield tunnel model based on the generalized response displacement method are established, respectively. Further, the seismic response of the shield tunnel is evaluated. The numerical results show that for the focus area: (1) The generalized response displacement method can consider the influences of topographic effects and site liquefaction slippage on the longitudinal seismic response of the shield tunnel. (2) The site slippage of bank slope is harmful to the safety of the large-diameter tunnel structure, as it may cause a large longitudinal opening width at the ring intersegment as well as sudden changes in section tension and pressure. (3) The bending moment variation curve and the acceleration amplification factor curve along the tunnel axis are consistent with the site topography, and the curves show obvious abrupt changes in the liquefied slippage areas.